PENGARUH KUALITAS PELAYANAN, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN E-COMMERCE SOCIOLLA - Putri, Aisyah Nabila; Putra, Angga Sanita (JPEKBM (Jurnal Pendidikan Ekonomi, Kewirausahaan, Bisnis dan Manajemen), 2022)
In the globalization era, the development of technology has become more advanced and given rise to the usage of internet within a majority of the population, causing many e-commerce business actors to use internet services for digital marketing, through both social media and marketplace platforms. An e-commerce participating in this advancement is Sociolla. The aim of this research is to see the perceptions of Sociolla users towards Service Quality, Price, Promotion, and Purchase Decisions, and to examine the effects of Service Quality, Price, and Promotion towards the Purchase Decisions in Sociolla Partially and Simultaneously. The method used in this research is the associative method with a quantitative research. Sample collection is done through the non-probability sampling method, and the non-probability sample collection method used is judgmental sampling, with a sample size of 100 respondents. The data analysis method uses the Validity and Reliability test, the Classic Assumption test, and the Hypothesis test.Based on the T test results, it is obtained that the variables Service Quality and Promotion pose a significant impact towards the Purchase Decisions in Sociolla, while Price does not pose a significant impact towards the Purchase Decisions in Sociolla. Concurrently, through the F test results, it is obtained that Service Quality, Price, and Promotion simultaneously pose a significat impact towards the Purchase Decisions in Sociolla.